Development of health belief in emerging infectious respiratory disease preventive behaviors' scale. (24th May 2022) - Cha, Hyosung; Lee, Kyungmi
Abstract: We developed a psychometric scale based on the Health Belief Model to predict preventive behaviors against emerging respiratory infectious diseases and verified its validity and reliability. Initial items on five constructs of the Health Belief Model were derived through focus group interviews and a literature review. These items were revised and supplemented through expert consultation to verify content validity. Data were collected from June 27, 2021, to July 5, 2021. We used the data of 201 adults aged 19–65 years for item analysis and assessment of construct, convergent, and discriminant validities and reliability. The final Health Belief in Emerging Infectious Respiratory Disease Preventive Behaviors' Scale (HB‐EIRD Preventive Behaviors' Scale) included 23 items on five factors, and cumulative explanatory variation was 63.0%. The fit indices were acceptable. Cronbach's α was 0.77. The scale can be scored 23–92; a higher score indicates stronger preventive behaviors. The HB‐EIRD Preventive Behaviors' Scale can be used to evaluate patients' health beliefs and predict preventive behaviors against emerging respiratory infectious diseases. This foundational knowledge can facilitate disease prevention and promote public health measures.